2020
DOI: 10.1111/jvim.15998
|View full text |Cite
|
Sign up to set email alerts
|

Correction of serum chloride concentration in dogs with congestive heart failure

Abstract: Background: Hypochloremia associated with congestive heart failure (CHF) in dogs is likely multifactorial. Loop diuretics cause 1:2 sodium [Na + ]:chloride [Cl − ] loss, whereas water retention causes a 1:1 [Na + ]:[Cl − ] dilution. Mathematical [Cl − ] correction separates these effects on [Cl − ]. Hypothesis: We hypothesized that corrected [Cl − ] (c[Cl − ]) would not differ from measured [Cl − ] (m[Cl − ]) in dogs with controlled CHF because of loop diuretics, and dogs with refractory CHF would have higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…One study 5 Other variables independently associated with uNa included serum Cl concentration and PCV, which likely reflect the importance of Cl on tubuloglomerular feedback and intravascular volume, respectively. 5,40 Some studies in humans found that the magnitude of hypochloremia was larger than hyponatremia, which might reflect the fact that the Na-K-2Cl cotransporter in the loop of Henle takes up 2 Cl for every 1 Na ion. 41 Chloride is the main electrolyte involved in the homeostatic or tubuloglomerular feedback system in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…One study 5 Other variables independently associated with uNa included serum Cl concentration and PCV, which likely reflect the importance of Cl on tubuloglomerular feedback and intravascular volume, respectively. 5,40 Some studies in humans found that the magnitude of hypochloremia was larger than hyponatremia, which might reflect the fact that the Na-K-2Cl cotransporter in the loop of Henle takes up 2 Cl for every 1 Na ion. 41 Chloride is the main electrolyte involved in the homeostatic or tubuloglomerular feedback system in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…We found inverse relationships between both calOsm and dmOsm with the amount of Cl À correction, which was expected and supports that the amount that serum Cl À changes after mathematical correction reflects water in the body, as previously proposed. 4 Interestingly, osmolality by either method was not correlated with serum Cl À concentrations or cCl À . Although Cl À impacts osmolality, its reciprocal relationship with HCO 3 À means that net negative osmoles are maintained even with hypochloremia.…”
Section: Comparisons Between Acute and Chronicmentioning
confidence: 92%
“…Mechanisms of hypochloremia include loop diuretic chloride wasting and volume expansion causing dilution. 58 , 65 , 69 In dogs, hypochloremia is associated with advanced disease and correlates with other markers of diuretic resistance such as uNa : uK <1. 58 , 70 Some studies indicated that hypochloremia was a stronger predictor of poor outcomes than hyponatremia in people with CHF.…”
Section: Diuretic Resistancementioning
confidence: 99%